ANALISIS WACANA KRITIS PADA KONTEN “MASJID UNTUK SEMUA” DI MEDIA YOUTUBE CISFORM UIN SUNAN KALIJAGA, YOGYAKARTA - Muhammad Irpan Nur (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
CISForm (Center for the Study of Islam and Sosial Transformation) is an institution that takes a role in the production of content on Youtube. By seeing how much content has been uploaded, this research examines the value contained in the content of CISForm. In this case, this research focusses on one content; namely